Bimbingan Pribadi-Sosial Untuk Mengembangkan Perilaku Moral Siswa - Raodhatul Jannah; Mamat Supriatna (Program Studi bimbingan Konseling PPs UNM Makassar, 2018)
The research is aimed to produce an effective social-personal guidance to develop students' moral behavior. This research uses quantitative approach with quasi experimental method and non-equivalent control group design to students class VIII of SMP Negeri 26 Bandung. Data analysis techniques used to find out the effectiveness of personal-social guidance in developing the moral behavior of students in SMP Negeri 26 Bandung Academic Year 2017/2018, include: 1) normality test; 2) homogeneity test; and 3) independent t test. The results show that in general social-personal guidance is not effective in developing students' moral behavior. But in particular there are five significant indicators, which is; 1) impose obligations as a child; 2) help others sincerely; 3) share / share information; 4) show concern for others; 5) guiding others to the task, and two insignificant indicators, namely; 1) understanding school rules; 2) consider the impact of lying.